Professional training conceptual foundations of future physical education teachers (Pedagogy of Higher and Secondary Education, 2013)
Belikovа N. O. Professional training conceptual foundations of future physical education teachers.Such conceptual framework of future physical education teachers’ training as intertwined properties (professional environment relevancy, innovation, communicativeness, transformation, comfort, democratization and predevelopment), principles and stages of this process has been defined and scientifically grounded.
Keywords: professional training; properties; principles; stages; future physical education teacher